Human pseudomyiasis caused by Eristalis tenax (Linnaeus) (Diptera: Syrphidae) in Goiás - Garcia-Zapata Marco Tulio A.; Souza Júnior Edson Sidião de; Fernandes Fernando Freitas; Santos Sônia F.O. (Sociedade Brasileira de Medicina Tropical (SBMT), 2005)
The objective of the present work was to register the first proven cases of human pseudomyiasis due to Eristalis tenax in Goiás State, Brazil, underscoring their clinical manifestations and direct relationship with hygiene. The taxonomic identification of the instars was done according to the descriptions and keys presented by James (1947), Hartley (1961) and Guimarães & Papavero (1999). Two cases were observed. In both cases there was no evidence of apparent mental disturbance. The clinical picture of these cases was self limited. The water supply, sewer system, socioeconomic level and habits of the suspect species of the flies are criteria that should be investigated.